Peningkatan Pengetahuan Siswa Sekolah Menengah Pertama Tentang Pertolongan Pertama pada Kecelakaan (P3K) - Rizki Andriani; Fitri Apriani; Erlia Rosita; Sri Mauliana Putri; Rosita Rosita; Safwan Yunita; Rohid Ramadanil; Riska Rahmalia (Universitas Teuku Umar, 2024)
First aid is essential for accident victims that can happen anywhere, including at school. This community service activity aims to increase student's knowledge, awareness, and skills in providing first aid to accident victims (P3K), especially in schools. P3K educational activities use lectures, discussions, leaflets, and demonstrations. The training participants were 35 SMPN 5 Meurebo Peunaga Ujong, West Aceh Regency students. The material presented includes essential life support, first aid for poisoning, choking, and allergies, wound care, and evacuation of accident victims. The demonstration was presented using audio-visual media, and this community service activity was evaluated using questionnaires given at the beginning and end of the activity. The results of this service activity showed that before P3K education was given, 71% of students had insufficient knowledge, and 29% had medium knowledge. After being given P3K education and demonstration, there was an increase in knowledge; namely, 34% of students had moderate knowledge, and 66% were highly knowledgeable. P3K education for students of SMPN 5 Meurebo Peunaga Ujong, West Aceh Regency, can improve students' knowledge and skills in performing first aid. Junior high school children are expected to act as first responders for victims of accidents that occur at school.